Allergy in severe asthma. Issue 2 (23rd November 2016) - Del Giacco, S. R.; Bakirtas, A.; Bel, E.; Custovic, A.; Diamant, Z.; Hamelmann, E.; Heffler, E.; Kalayci, Ö.; Saglani, S.; Sergejeva, S.; Seys, S.; Simpson, A.; et al.
Abstract: It is well recognized that atopic sensitization is an important risk factor for asthma, both in adults and in children. However, the role of allergy in severe asthma is still under debate. The term 'Severe Asthma' encompasses a highly heterogeneous group of patients who require treatment on steps 4–5 of GINA guidelines to prevent their asthma from becoming 'uncontrolled', or whose disease remains 'uncontrolled' despite this therapy. Epidemiological studies on emergency room visits and hospital admissions for asthma suggest the important role of allergy in asthma exacerbations. In addition, allergic asthma in childhood is often associated with severe asthma in adulthood. A strong association exists between asthma exacerbations and respiratory viral infections, and interaction between viruses and allergy further increases the risk of asthma exacerbations. Furthermore, fungal allergy has been shown to play an important role in severe asthma. Other contributing factors include smoking, pollution and work‐related exposures. The 'Allergy and Asthma Severity' EAACI Task Force examined the current evidence and produced this position document on the role of allergy in severe asthma. Abstract :